Two-step melting of the Weeks-Chandler-Anderson system in two dimensions. - Khali, Shubhendu Shekhar (Royal Society of Chemistry, 2021)
We present a detailed numerical simulation study of a two-dimensional system of particles interacting via the Weeks–Chandler–Anderson potential, the repulsive part of the Lennard-Jones potential. With the reduction of density, the system shows a two-step melting: a continuous melting of solid to hexatic phase, followed by a first-order melting of hexatic to liquid. The solid–hexatic melting is consistent with the Berezinskii–Kosterlitz–Thouless–Halperin–Nelson–Young (BKTHNY) scenario and shows dislocation unbinding. The first-order melting of the hexatic to the liquid phase, on the other hand, displays defect-strings formed at the hexatic–liquid interfaces. We present a detailed phase diagram in the density-temperature plane.
Only IISER Mohali authors are available in the record.
Keywords: Weeks–Chandler–Anderson